Oral Health and Lifestyle Factors in Rural Adults of Jharkhand, India - Sandeep Kumar; null Anubhuti; Abhishek Gautam; Ambar Khan; Anita B; Punit Karmacharya (Hindawi Limited, 2024)
Background. There is a lack of health care facilities and poor oral health awareness among the rural adult population of Jharkhand which may significantly influence oral health status and lifestyle scores. Aim. To assess the oral hygiene status, lifestyle factors, and various risk factors associated with poor lifestyle scores in the rural adult population of Jharkhand. Materials and Methods. This cross-sectional study included 400 rural adults (35-44 years) populations. Face-to-face interviews were used to collect sociodemographic data and data on oral hygiene practices. Lifestyle factors were assessed using Health Practice Index (HPI). Oral health status was assessed using the oral health assessment proforma provided by the World Health Organization (WHO). Results. A significantly higher (p value < 0.0001) prevalence of tobacco consumption was reported by males (94.0%) compared to females (4.0%). The males (54.0%) reported significantly higher (p value < 0.0001) poor lifestyle scores compared to females (38.0%). A significantly higher (p value < 0.0001) number of oromucosal lesions (13.0%) was found in males compared to females (1.0%). There was a significant difference (p value < 0.0001) in the oral hygiene status between males and females with majority of males (60.0%) having poor oral hygiene. A bivariate analysis was performed, and unadjusted odds ratio was computed. The factors that became significant were then entered into logistic regression model (enter method). The results of logistic regression analysis showed that education (OR = 0.3, p value = 0.003), systemic diseases/long-term medication (OR = 2.9, p value = 0.004), tobacco consumption (OR = 2.9, p value = 0.006), oral hygiene status (OR = 2.4, p value = 0.007), and dental caries (OR = 2.9, p value = 0.004) were significant predictors of poor lifestyle scores. Conclusion. The rural adult population in Jharkhand has poor oral hygiene status and poor lifestyle scores. It is important to raise awareness regarding good oral hygiene and the negative effects of tobacco consumption. The dental visit should be encouraged, and the concept of preventive care needs to be instilled.